1999
DOI: 10.2105/ajph.89.7.1009
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to diesel exhaust and lung cancer: a meta-analysis.

Abstract: Numerous epidemiological investigations have examined whether occupational exposure to diesel exhaust is associated with lung cancer. Although several recent reviews have concluded that the evidence is consistent with a causal relationship, others have not.14 A meta-analysis cannot prove or disprove causality per se; however, it can explore the basis for differences among studies and in so doing provide evidence bearing on causal inference. Materials and Methods Identification and Selection ofStudies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(127 citation statements)
references
References 59 publications
5
121
0
1
Order By: Relevance
“…Overall, occupational exposures to motor vehicle exhausts, including diesel engine fumes, have been related with increased lung cancer risk in bus and truck drivers and other traffic-exposed workers, 31,32 with 2 recent meta-analyses reporting pooled estimates around 1.5. 33,34 Our results suggest that XPD, a polymorphic gene involved in nucleotide excision DNA repair, 14 might play an important role in repairing bulky DNA adducts in human leukocytes, particularly those induced from traffic environmental carcinogens, in keeping with a previous study. 11 A similar, although not statistically significant, effect was possibly suggested also for XRCC1, in agreement with the studies by Lunn et al 12 and Duell et al 16 A still weaker effect was shown for XRCC3-241 polymorphism for which, however, evidence of its possible involvement in DNAadducts repair has been provided.…”
Section: Multivariate Analysissupporting
confidence: 89%
“…Overall, occupational exposures to motor vehicle exhausts, including diesel engine fumes, have been related with increased lung cancer risk in bus and truck drivers and other traffic-exposed workers, 31,32 with 2 recent meta-analyses reporting pooled estimates around 1.5. 33,34 Our results suggest that XPD, a polymorphic gene involved in nucleotide excision DNA repair, 14 might play an important role in repairing bulky DNA adducts in human leukocytes, particularly those induced from traffic environmental carcinogens, in keeping with a previous study. 11 A similar, although not statistically significant, effect was possibly suggested also for XRCC1, in agreement with the studies by Lunn et al 12 and Duell et al 16 A still weaker effect was shown for XRCC3-241 polymorphism for which, however, evidence of its possible involvement in DNAadducts repair has been provided.…”
Section: Multivariate Analysissupporting
confidence: 89%
“…Furthermore, numerous studies show a higher risk for lung cancer among populations occupationally exposed to diesel engine exhaust (28). It is difficult to disentangle the effect of single air pollutants in epidemiologic designs because they are part of complex mixtures.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found an association between occupational exposure to diesel exhaust and lung cancer. 75 On the basis of extensive toxicologic and epidemiologic evidence, national and international health authorities, including the EPA and the International Agency for Research on Cancer, have concluded that there is considerable evidence of an association between exposure to diesel exhaust and an increased risk of lung cancer. 76,77 Additionally, fine particles in diesel exhaust may enhance allergic and inflammatory responses to antigen challenge and may facilitate development of new allergies.…”
Section: Traffic-related Pollutionmentioning
confidence: 99%